MENINGKATKAN PROSES DAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI PENERAPAN MULTIMEDIA INTERAKTIF (POWER POINT) - RE.FATIMAH (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2013)
The problems to be examined in this study are : ( a) How does an increase in student achievement with the implementation of teaching Through Interactive Multimedia Approach ( Power Point ) Child -Centered to Increased Creativity ? The purpose of this research is to develop a model of Islamic Learning -Based Interactive Multimedia for primary school students . The research approach used in this study is to develop a model approach to research and development ( Research and Development ) with the modification of action research ( PTK ) This research was conducted in class V SDN Duri Kosambi, West Jakarta 01 Morning consisting of 30 students . The method used was Classroom Action Research ( CAR ) model of Kemmis and Taggart (1990 ) . The instrument used in the form of observation sheets , multiple choice questions , about the description , and student questionnaire responses . Learning is done as much as two cycles , each cycle consisting of 2 meetings . In general, learning can proceed smoothly and in accordance with the RPP , by doing reflection in each cycle of problems that arise can be resolved properly . The average value of learning outcomes in the pre-action amounted to 53.96 , 78.04 for cycle 1 and cycle 2 is 83.33 . Results of tests of creative thinking of students in cycle 1 at 68.01 and has increased in cycle 2 at 72.51 . A positive response in cycle 1 was 58.65 % increase in cycle 2 was 70.99 % . Overall it can be seen that the use of interactive multimedia learning can improve learning outcomes , students' creative thinking and response . So learning using interactive multimedia as an effort to improve learning outcomes and student creative thinking has been successfully implemented